Estudos de novas rotas para a síntese estereosseletiva da (-)-citoxazona e da (+)-5-epi-citoxazona e ensaios de atividade antibacteriana - Izabel Luzia Miranda (2019)
Oxazolidinones comprise a class of natural and synthetic compounds which exhibit antibacterial activity against a wide variety of Gram-positive bacteria. In this class, ()-cytoxazone and its isomers, such as (+)-5-epi-cytoxazone, stand out. In the present work, new synthetic stereoselective routes were developed from chiral substrates, D-4-hydroxyphenylglycine that provided the ()-cytoxazone and (+)-5-epi-cytoxazone and D-mannitol, which provided (+)-5- epi-cytoxazone. The first approach to the synthesis of ()-cytoxazone and (+)-5-epi-cytoxazone was performed in 9 steps, with overall yields of 6 and 14%, respectively, from D-4- hydroxyphenylglycine. The main step of this approach is based on the stereoselective addition of NaCN to the protected N-Boc amino (N-Boc) (tent-butyl ((R)-1-(4-methoxypheny1)-2- oxoethyl] carbamate) which provided the mixture of the cyanohydrins, 2-cyano-2-hydroxy-1- (4-methoxyphenyflethyl) carbamate, 1,2-anti and 1,2-syn in 89% yield. This step showed a reasonable stereoselectivity (1.0:1.84) in favor of the anti-Felkin-Anh product, the 1,2-syn cyanohydrin, precursor of (+)-5-epi-cytoxazone. The mixture of these cyanohydrins could not be separated by column chromatography. The following steps were carried out with the mixture to obtain the oxazolidinonic (4R,5R)- and (4R,55)-4-(4-methoxypheny1)-2-oxazolidine-5- carboxylates of methyl isomers (83 and 84). This new mixture was separated by column chromatography, allowing to determine the stereoselectivity obtained in the cyanide addition step. Finally, derivatives 83 and 84 were individually subjected to ester function reduction reactions, leading to ()-cytoxazone and (+)-5-epi-cytoxazone. The second strategy for the synthesis of the oxazolidinone ring produced 5-epi-cytoxazone, a non-natural isomer in 8 steps in overall yield of 17% via a new route from 2,3-0-(3-pentylidene)- (R)-glyceraldehyde (90), derived from D-mannitol as the chiral starting material. This strategy was based on two fundamental pillars. The Wittig olefination reaction between the (R)- glyceraldehyde ketal (90) and the ylide generated from (4-methoxy-benzy1)- triphenylphosphonium chloride led to the preferential formation of the (S, Z)-2,2-diethy1-4-(4- methoxystyry1)-1,3-dioxolane (88a) (Z:E 4:1) after extensive efforts for chromatographic column purification. In the other key step, the volatile ketal alkene group (88a) allowed the intramolecular control of the asymmetric centers of the target molecule in the dihydroxylation, promoted by the approximation of 0s04 to the opposite face to the volumetric ketal group, providing the majority formation of (1S,2S)-14(R)-2,2-diethy1-1,3-dioxolan-4-y1)-2-(4- methoxyphenyl) ethane-1,2-diol (87a), named anti (6: 1), in 72% yield after separation of the mixture by column chromatography. Subsequent steps from diol 87a, sulfocyclization, regioselective open of the sulphite ring with sodium azide, reduction of the azide group and N,0-heterocyclization led to (4R,5S)-5-[(1R)-1,2-dihydroxyethy1]-4-(4-methoxypheny1)-1,3- oxazolidin-2-one (93). Finally, oxidative cleavage of diol 93 and reduction of the resulting aldehyde gave (+)-5-epi-cytoxazone in 79% yield (two steps). The specific rotation values found for ()-cytoxazone and (+)-5-epi-citoxazone were in agreement with those described in the literature. Preliminary assays for determination of minimal inhibitory concentration (MIC) against S. aureus strains were performed employing the intermediates (1S,2R)-2-amino-14(R)-2,2-diethy1-1,3-dioxolan-4-y1)-2-(4-methoxyphenyl) ethanol (85), 93 as well as (+)-5-epi-cytoxazone, pointing to aminoalcohol 85 as a potential antibacterial agent, having an MIC of 0.25 mg/mL for S. aureus strains 8923, 9000 and 9005, and 0.12 mg/mL for strains S. aureus 8907 and 8908.